Influence of acute and chronic intermittent hypoxic-hyperoxic exposure prior to aerobic exercise on cardiovascular risk factors in geriatric patients—a randomized controlled trial - Behrendt, Tom; Altorjay, Ann-Christin; Bielitzki, Robert; Behrens, Martin; Glazachev, Oleg S.; Schega, Lutz (Frontiers in Physiology, 2022)
Background: Intermittent hypoxic-hyperoxic exposure (IHHE) and aerobic training have been proposed as non-pharmacological interventions to reduce age-related risk factors. However, no study has yet examined the effects of IHHE before aerobic exercise on cardiovascular risk factors in the elderly. Therefore, the aim of this study was to investigate the acute and chronic effects of IHHE prior to aerobic cycling exercise on blood lipid and lipoprotein concentrations as well as blood pressure in geriatric patients. Methods: In a randomized, controlled, and single-blinded trial, thirty geriatric patients (72-94 years) were assigned to two groups: intervention (IG; n=16) and sham control group (CG; n=14). Both groups completed 6 weeks of aerobic cycling training, 3 times a week for 20 min per day. The IG and CG were additionally exposed to IHHE or sham IHHE (i.e., normoxia) for 30 min prior to aerobic cycling. Blood samples were taken on three occasions: immediately before the first, ~10 min after the first, and immediately before the last session. Blood samples were analyzed for total (tCh), high-density (HDL-C), and low-density lipoprotein cholesterol (LDL-C), and triglyceride (Tgl) serum concentration. Resting systolic (SBP) and diastolic blood pressure (DBP) was assessed within one week before, during (i.e., at week two and four), and after the interventions. Results: The baseline-adjusted ANCOVA revealed a higher LDL-C concentration in the IG compared to the CG after the first intervention session (p²=0.12). For tCh, HDL-C, Tgl, and tCh/HDL-C ratio there were no differences in acute changes between the IG and the CG (p20.01). With regard to the chronic effects on lipids and lipoproteins, data analysis indicated no differences between groups (p20.03). The repeated measures ANOVA revealed an interaction effect for SBP (p2=0.06) but not for DBP (p20.01). Within-group post-hoc analysis for the IG indicated a reduction in SBP at post-test (d=0.05). Conclusion: Applying IHHE prior to aerobic cycling seems to be effective to reduce SBP in geriatric patients after 6 weeks of training. The present study suggests that IHHE prior to aerobic cycling can influence the acute exercise-related responses in LDL-C concentration but did not induce chronic changes in basal lipid or lipoprotein concentrations.